Organizational Modes and Water Service Performance: A 1995–2025 Meta-Analysis and Implications for PPPs and Regional Multiservice Companies (SRMs) in Morocco - Elouafai, Mohamed Charaf; Azegagh, Jalal (European Scientific Journal, ESJ, 2025)
Across LMICs, water governance varies; Morocco combines public régies, ONEE, delegated PPPs, and new SRMs, complicating evidence on “what works”. Following PRISMA, a meta-analysis (1995–2025; 173 studies; 742 effects) harmonized efficiency, access, quality, equity, environmental, and governance outcomes with moderators. Pooled results favor PPP/delegated modes for efficiency (g≈0.22) and modestly for access and quality; equity tends negative; environmental effects are near zero. Regulatory capacity, KPI breadth, and yardstick competition strengthen performance; ownership alone is not decisive. In Morocco, SRM regionalization should embed transparent benchmarking and social tariffs to balance efficiency with inclusion.